Prevalence and determinants of high risk human papilloma virus in Hyderabad, India - V., Chandana; Gaguturu, Rasheeda Begum (International Journal of Reproduction, Contraception, Obstetrics and Gynecology, 2018)
Background: Cervical cancer is the most common cancer among india women and age standardized mortality rate are the highest in south central Asia. In the past decade an among aetiologic association between infection with high risk human papilloma virus and development of cervical cancer has been increased. The study was aimed at studying the prevalence and determinants of high risk human papilloma virus in these patients. Methods: This study was conducted for a period of one year to know the prevalence and determinants of high risk human papilloma virus in the patients attending gynaec out patient department. A total of 266 married women between 15-75 were randomly selected for the study. Results: There is high prevalence of HPV in low (43.3%)/mid (37.4%) socio economic class (17.6%). But the result was not statistically significant (p=0.149). higher prevalence of HPV was found in multiparas (39.4%) compared to multiparas (33.3%) which was not statistically significant (p=0.233). Husbands of 252 women were circumcised out of which 96 wives were positive for HPV DNA (38.1%). Among 14 women with no history of circumcision in their husband HPV DNA positive (28.6%). Correlation of cytology with HPV DNA among different age groups showed increasing prevalence with age but the result was not statistically significant (p=0.115). the result showed that age at marriage, higher the prevalence of HPV DNA. The result was statistically significant (p=0.017). with increasing state of education, the prevalence of HPV infection decreased, but the result was not statically significant (p=0.142).51.3% of women of who were not education were positive for HPV as against only 25% of graduates were HPV positive. Conclusions: Genital hygiene, genetic polymorphisms and other environmental cofactors among HPV DNA positive women, which prevent oncogenesis.